Analisa Pengaruh Temperatur Terhadap Laju Pengeringan Crumb Rubber Pada Dryer Menggunakan Energi Panas Pembakaran Pada Burner - Simanjuntak, Agus Wiranto; Darmadi, Herry; Rahmansyah, Abdul Azis; Nelza, Novia; Bukhari, Bukhari (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2023)
Crumb rubber is a semi-finished natural rubber product that still contains moisture content. One of the most needed crumb rubber standards is SIR 20 (crumb rubber) with a maximum moisture content of 0.80% according to Indonesia National Standard. To remove the water content, it is necessary to carry out the drying process. Drying is a process to evaporate water in a material by using heat. The drying process is carried out in the dryer unit. Hot air is obtained from burning a burner with a temperature of 130°C. The burner will heat the air and then distribute the hot air to the dryer unit with a dryer temperature of 116°C. In the dryer unit, crumb rubber will be dried with a drying process time of 172.62 minutes. The total heat required to dry the crumb rubber with an incoming feed weight of 626.66 kg, and the moisture content of the crumb rubber after drying is an average of 0.53%, this result still meets the standards of crumb rubber. ) SIR 20 of a maximum of 0.80%.